Władysław Heinrich's philosophy of nature - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
At the turn of the 19th and 20th century, Wladyslaw Heinrich introduced a new style of philosophizing in the Cracow rather traditional philosophical milieu. His way of presenting philosophical ideas in a strict contact with empirical sciences arose great interest and found several talented followers. In the Jagiellonian Library in Cracow the manuscript is preserved bearing the title 'Theory of Cognition'; it was written by Heinrich in 1912. The author presents and critically assesses his 'philosophy of nature' as it can be reconstructed from the above mentioned manuscript.